Daya Simpan Susu Pasteurisasi Ditinjau dari Kualitas Mikroba Termodurik dan Kualitas Kimia - Novita Dewi Kristanti (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2017)
The aim of this study was to determine the quality of thermoduric bacteria and chemical quality of pasteurized milk stored with different time periods. The material was milk from the farmers that was pasteurized at 950C for 21 seconds. The research Method used completely randomized design. The variables observed were TPC, Koliform, Kapang, E. coli bacteria, fat content, protein content, lactose content, total solid, and solid non fat (SNF). The results of the study showed that E. coli and Koliform were not found in pasteurized milk, but a number of thermoduric microbes wereÂ  found. Pasteurized milk has a shelf life of 30 days under 40C Â± 10C conditions and has no significant changes in fat content, lactose levels, non-fat dry matter content and protein content.